Effect of SARS-CoV-2 spike protein exposure on ACE2 and interleukin 6 productions in human adipocytes: An in-vitro study - Ardiana, Meity; Suryawan, I GR.; Hermawan, Hanestya O.; Harsono, Primasitha M.; Shafira, Aisya A.; Anandita, Faizal A. (Narra Sains Indonesia, 2023)
Since adipocytes play a crucial role in pathogenesis of severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2) infection due to their interaction with angiotensin-converting enzyme 2 (ACE2) and interleukin 6 (IL-6), obesity is associated with an increased risk of coronavirus disease 2019 (COVID-19) mortality. Discovery of ACE2 as a SARS-CoV-2 receptor raises a controversy about whether to use ACE inhibitors (ACEIs) could be an optional therapy to prevent cytokine storms. Studies assessing the expressions of ACE2 and IL-6 upon exposure to SARS‑CoV‑2 is therefore important as a basis for therapeutical trials in the future. The aim of this study was to determine the effect of SARS-CoV-2 spike protein exposure on the production of ACE2 and IL-6 in adipocyte cells. Adipocytes were collected from abdominal adipose tissues of healthy and obese 45-year-old male donor having neither a history of SARS‑CoV‑2 infection nor COVID-19 vaccination. After being stained using the oil red O protocol, the viable adipocytes were then exposed to S1 subunit of SARS-CoV-2 spike protein. The levels of ACE2 and IL-6 were then examined using the enzyme-linked immunosorbent assay (ELISA). The results showed significant increase of ACE2 (90.22 µg/mL) and IL-6 level (60.01 µg/mL) in human adipocytes upon exposure compared to unexposed control cells (ACE2 13.33 µg/mL; IL-6 21.33 µg/mL), both comparisons had p<0.001). This study provides insight into the basic mechanism of severe COVID-19 symptoms in obese patients and provides a basic information of the potential of ACE inhibitors as an optional therapy for COVID-19 patients with obesity.